Climate Change as Inhuman Treatment - Jelena Belic (Global justice: Theory, Practice, Rhetoric)
In one of the most recent climate litigation cases, Duarte Agostinho and Others v. Portugal and Others, the European Court of Human Rights asked the responding states to consider whether their inaction concerning climate change affects the applicants’ rights under article 3 of the European Convention of Human Rights (i.e. the prohibition of torture or inhuman or degrading treatment or punishment). What makes the invocation of article 3 distinctive is that it involves a very narrow set of absolute rights; that is, the rights that are not subject to the proportionality test, and which correlate with legal obligations that are non-derogable and non-negotiable even in times of war or other public emergencies. Therefore, finding that anthropogenic climate change violates the rights against torture, or inhuman or degrading treatment may have potentially significant legal consequences and accordingly, may further strengthen the human rights approach to climate change. Finding the violation of said prohibitions, however, is easier said than done since there are many hurdles some of which relate to human rights in general, and others that are distinctive of the said prohibitions, including the lack of specified normative foundations.